2005
DOI: 10.1097/01.bot.0000177107.30837.61
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver Reliability of a CT-Based Fracture Classification System

Abstract: The results indicate that in a carefully controlled paradigm, the interobserver reliability with a classification system based on interpretation of a single, carefully defined CT image was no better than the results reported for the same classification system used with full CT data or for other classification systems used for various fractures in the skeleton. Agreement in identifying the location of the fracture lines was very good for simple fractures but much worse for complex injuries. Additional study may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 25 publications
2
34
0
4
Order By: Relevance
“…We used observers with different levels of experience in the assessment of calcaneal fractures in both clinical and research context. Earlier studies have shown that the level of experience of the observers, and the complexity of the classification system, do not usually affect inter-observer reliability [27]. Our study will help guide future researchers in their choice of grading system when reporting on posttraumatic subtalar osteoarthritis, and assist in the comparison of different treatment modalities for calcaneal fractures.…”
Section: Discussionmentioning
confidence: 75%
“…We used observers with different levels of experience in the assessment of calcaneal fractures in both clinical and research context. Earlier studies have shown that the level of experience of the observers, and the complexity of the classification system, do not usually affect inter-observer reliability [27]. Our study will help guide future researchers in their choice of grading system when reporting on posttraumatic subtalar osteoarthritis, and assist in the comparison of different treatment modalities for calcaneal fractures.…”
Section: Discussionmentioning
confidence: 75%
“…It is difficult to compare outcome between studies since different measures of outcome are often used and there is no consensus among surgeons as to which is the most scientific and practical system. Although classifications show positive correlation with outcome,there is no correlation with choice of treatment 21,22 . In our study we have used Essex-Lopresti and Sander"s classification.…”
Section: Discussionmentioning
confidence: 98%
“…Humphrey et al 9 evaluated whether a limitation of the available CT data may lead to better inter-and intraobserver reliability when classifying calcaneal fractures with the Sanders system. In their study, fracture classification was performed on the basis of a single carefully defined CT cut.…”
Section: Discussionmentioning
confidence: 99%